Radiolabeled oligonucleotides targeting the RNA subunit of telomerase inhibit telomerase and induce DNA damage in telomerase-positive cancer cells - Jackson, MR; Bavelaar, BM; Waghorn, PA; Gill, MA; El-Sagheer, AH; Brown, T; Tarsounas, M; Vallis, K (American Association for Cancer Research, 2019)
Telomerase is expressed in the majority (>85%) of tumours, but has restricted expression in normal tissues. Long-term telomerase inhibition in malignant cells results in progressive telomere shortening and reduction in cell proliferation. Here we report the synthesis and characterisation of radiolabeled oligonucleotides that target the RNA subunit of telomerase, hTR, simultaneously inhibiting enzymatic activity and delivering radiation intracellularly. Oligonucleotides complementary (match) and non-complementary (scramble or mismatch) to hTR were conjugated to diethylenetriaminepentaacetic dianhydride (DTPA), allowing radiolabeling with the Auger electron-emitting radionuclide indium-111 (111In). Match oligonucleotides inhibited telomerase activity with high potency which was not observed with scramble or mismatch oligonucleotides. DTPA-conjugation and 111In-labeling did not change telomerase inhibition. In telomerase-positive cancer cells, unlabeled match oligonucleotides had no effect on survival, however, 111In-labeled match oligonucleotides significantly reduced clonogenic survival and upregulated the DNA damage marker γH2AX. Minimal radiotoxicity and DNA damage was observed in telomerase-negative cells exposed to 111In-match oligonucleotides. Match oligonucleotides localised in close proximity to nuclear Cajal bodies in telomerase-positive cells. In comparison to match oligonucleotides, 111In-scramble or 111In-mismatch oligonucleotides demonstrated reduced retention and negligible impact on cell survival. This study indicates the therapeutic activity of radiolabeled oligonucleotides that specifically target hTR through potent telomerase inhibition and DNA damage induction in telomerase-expressing cancer cells, and paves way for the development of novel oligonucleotide radiotherapeutics targeting telomerase-positive cancers.